2007
DOI: 10.1073/pnas.0708699104
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ionotropic AMPA receptor 3 alter channel properties and are associated with moderate cognitive impairment in humans

Abstract: Ionotropic ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors (iGluRs) mediate the majority of excitatory synaptic transmission in the CNS and are essential for the induction and maintenance of long-term potentiation and long-term depression, two cellular models of learning and memory. We identified a genomic deletion (0.4 Mb) involving the entire GRIA3 (encoding iGluR3) by using an X-array comparative genomic hybridization (CGH) and four missense variants (G833R, M706T, R631S, and R450Q) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 32 publications
4
89
0
2
Order By: Relevance
“…In addition, CUL4B (OMIM 300304) and GRIA3 (OMIM 305915), which were reported as XLMRassociated genes, 41,42 are located around the region involved (Supplementary Figure S4g). It is possible that the deletion alters expression levels through some mechanism, such as a defect in binding of transcription factor(s) and alteration of the chromatin structure.…”
Section: Cnvs In Xlmr S Honda Et Almentioning
confidence: 99%
“…In addition, CUL4B (OMIM 300304) and GRIA3 (OMIM 305915), which were reported as XLMRassociated genes, 41,42 are located around the region involved (Supplementary Figure S4g). It is possible that the deletion alters expression levels through some mechanism, such as a defect in binding of transcription factor(s) and alteration of the chromatin structure.…”
Section: Cnvs In Xlmr S Honda Et Almentioning
confidence: 99%
“…72 In addition, one genetic study reported that GRIA3 gene mutations were related to moderate cognitive impairment in humans. 73 Furthermore, another line of evidence from animal studies has suggested a potentially compensatory role of AMPA receptors following NMDA receptor dysfunction. [74][75][76] For example, Jackson et al 77 demonstrated that an increase in glutamate efflux by NMDA antagonists stimulated cortical AMPA receptors.…”
Section: Findings By Analyses Of Individual Drugs and Subgroup Analysesmentioning
confidence: 99%
“…For the GRIA gene family, there have been reports of a fusion transcript in GRIA2, a de novo interstitial deletion of chromosome 4q32 that contains the GRIA2 loci, missense mutations in the ligand binding and transmembrane domains of the GluA3 subunit (GRIA3), partial tandem duplication that reduced GRIA3 transcript levels, as well as frameshift in the GRIA3 gene ( Fig. 5; Supplemental Table S3) (Chiyonobu et al, 2007;Wu et al, 2007;Bonnet et al, 2009Bonnet et al, , 2012Poot et al, 2010;Tzschach et al, 2010;Hackmann et al, 2013;Philips et al, 2014). These data suggest that mutations within the GRIA gene family participate in a small subset of patients with intellectual disability; however, few cellular or mechanistic studies of these modifications have been reported.…”
Section: Ampa-selective Glutamate Receptorsmentioning
confidence: 99%